Evaluation of pain intensity and airway changes in non-growing patients treated by MARPE with and without micro-osteoperforation: a randomized clinical trial - Moataz Elshehaby; Nehal Fouad Albelasy; Mohamed A. Elbialy; Ahmad Mohammed Hafez; Yasser Lotfy Abdelnaby (BMC, 2024)
Abstract Trial design Parallel. Objectives To assess the effect of mini-screw assisted rapid palatal expansion (MARPE) with/without micro-osteoperforation (MOP) on the airway and pain intensity in non-growing patients with maxillary transverse deficiency. Method Two equal groups of twenty-four individuals aged ≥ 19 years old with maxillary transverse deficit were randomly assigned. MOP-facilitated MARPE was used to treat one group (MMG), and the other group was treated with MARPE without MOP (NMG). For airway evaluation, CBCT images were obtained 2 months before starting the palatal expansion and 3 months after finishing the expansion in 28 days. The Visual Analogue Scale (VAS) was used to measure the pain level. Results Significant suture opening was observed in both groups. All linear measurements of the nasal cavity and volumetric measurements of the nasal passage and oropharyngeal airway increased significantly in both groups, with no significant difference between them. Moderate pain was experienced in the first two weeks of expansion in MMG (5.11 ± 0.30), while more significant pain was recorded in NMG (6.87 ± 0.40). Pain decreased significantly in the following two weeks in MMG (2.77 ± 0.39) and in NMG (5.11 ± 0.32), with a significant difference between the two groups throughout the entire duration of expansion. Conclusion Transverse maxillary deficit was successfully treated with both expansion methods, with and without MOP, with comparable skeletal effects at the nasal levels and airway volumetric improvement. So, MOP did not provide any further advantage in improving the airway volume after maxillary expansion. However, it significantly reduced pain intensity throughout the entire duration of expansion. Trial registration The protocol registration and results system (PRS) of ClinicalTrials.gov has this RCT registered under the number NCT06502041 on 13/07/2024.